1998
DOI: 10.1144/gsjgs.155.5.0873
|View full text |Cite
|
Sign up to set email alerts
|

Granular flow and viscous fluctuations in low Bagnold number granitic magmas

Abstract: Recent thermal and fluid dynamical models have shown that density-driven ascent of isoviscous granitic melt through the crust in narrow dykes is geologically instantaneous, provided the role of suspended crystals is ignored. However, it is well known that solids in suspension can aVect significantly the rheology and hence flow properties of magmas, leading to the subjective criticism that granite ascent and emplacement rates based on simple dyke transport models may be unrealistic. By estimating the magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The behaviour of natural magmas may be described by granular flow theory and, until the magma has stopped, deviation from simple Newtonian flow is unlikely (Petford & Koenders 1998). Gravity-controlled crystals accumulation.…”
Section: The Processes Operating During Formation Of Magmatic Layeringmentioning
confidence: 99%
“…The behaviour of natural magmas may be described by granular flow theory and, until the magma has stopped, deviation from simple Newtonian flow is unlikely (Petford & Koenders 1998). Gravity-controlled crystals accumulation.…”
Section: The Processes Operating During Formation Of Magmatic Layeringmentioning
confidence: 99%
“…Pinkerton and Stevenson (1992) suggested that yield strength was only developed in materials containing at least 30 vol.% crystals. Petford and Koenders (1998) consider that a Bingham model is inappropriate for millimeter to centimeter grain size, which applies to most intermediate to silicic magmas. This observation that we have no definitive evidence for the existence of a yield strength at magmatic temperatures for about 30 vol.% crystals or more is in conflict with many other studies on crystal-bearing melts (Petford and Koenders 1998;Hoover et al 2001;Petford 2003), but it may be due to the difficulties of measuring yield strength (Nguyen and Boger 1992;Moller et al 2006;Ishibashi and Sato 2007) and it can also be due to the extreme sensitivity of this parameter to the crystal shape (Hoover et al 2001), volume fraction, and alignment (Walsh and Saar 2008).…”
Section: Yield Strength Of Dacitic Lava At Magmatic Temperaturesmentioning
confidence: 99%
“…The latter have been derived for a smooth boundary (McTigue and Jenkins, 1992), but not for rough boundaries, a more realistic natural situation where magma is flowing in dykes and sills with irregular walls. A solution to this problem was obtained for the first time by Petford and Koenders (1998) for granitic magmas flowing vertically in a dyke. They showed that the accompanying fluctuation in velocity intensity resulted in a granular velocity fluctuation intensity that was greatest closest to the dyke walls, as expected from theory.…”
Section: Shear-aided Particle Migrationmentioning
confidence: 99%